Regulating Halal Integrity in Sri Lanka: A Comparative Legal and Shariah Analysis of the Food Act and Consumer Protection Framework - Saujan, Iqbal; Nafees, Seeni Mohamed Mohamed; Fowzul, Mohamed Buhary (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2026)
The global hal?l market is a huge economic power, demanding products that are very compliant with Islamic rules. In Sri Lanka, a country where Muslims make up a large minority and where there has been social tension due to this, the merging of the national food laws with the shari’ah requirments concerning hal?l integrity creates issues in regulation. Therefore, this paper looks into the existing statutory framework of Sri Lanka, mainly focusing on Food Act No. 26 of 1980 and Consumer Affairs Authority Act No. 9 of 2003, along with detailed shari’ah requirements related to hal?l food including slaughter (zabiha), ingredients, processing and prevention of contamination. The study, by way of comparative legal analysis and considering academic literature and international regulatory models (Malaysia, Indonesia, UAE, EU), places where the Sri Lankan law defining, regulating, and certifying. and enforcing hal?l standards falls short. The particulars revealed that there were no specific legal definitions and standards for hal?l. Oversight of the certification processes is inadequate. There are no adequate mechanisms preventing hal?l cross-contamination between hal?l/non-hal?li and labelling regulations do not include provisions for a legally recognized hal?l mark. These shortcomings create consumer ambiguity business challenges and conflict potential. It proposes legislative changes to the Food Act and its related regulations, along with the setting up of an administrative framework which is likely to be national accreditation supervision of private certifiers, state-regulated. The proposals emanate from Islamic jurisprudence (Maqasid al-Shari'ah and Fiqh principles) and they are directed toward ensuring legal certainty, improved consumer protection, enhanced trade facilitation, and social harmony in a multi-religious context such as that of Sri Lanka. [Pasar halal global merupakan kekuatan ekonomi yang besar, menuntut produk-produk yang sangat patuh terhadap aturan Islam. Di Sri Lanka, sebuah negara di mana Muslim merupakan kelompok minoritas besar dan di mana telah terjadi ketegangan sosial akibat hal ini, penggabungan antara undang-undang pangan nasional dengan persyaratan syariah terkait integritas halal menciptakan masalah dalam regulasi. Oleh karena itu, makalah ini menelaah kerangka hukum yang ada di Sri Lanka, dengan fokus utama pada Food Act No. 26 Tahun 1980 dan Consumer Affairs Authority Act No. 9 Tahun 2003, beserta syarat-syarat syariah terkait makanan halal secara rinci, termasuk penyembelihan (zabiha), bahan-bahan, pemrosesan, dan pencegahan kontaminasi. Studi ini, melalui analisis hukum komparatif dan dengan mempertimbangkan literatur akademik serta model regulasi internasional (Malaysia, Indonesia, UEA, UE), menunjukkan di mana hukum Sri Lanka mengenai pendefinisian, pengaturan, sertifikasi, dan penegakan standar halal masih kurang. Rincian yang terungkap menunjukkan bahwa tidak ada definisi hukum dan standar khusus untuk halal. Pengawasan terhadap proses sertifikasi juga tidak memadai. Tidak terdapat mekanisme yang memadai untuk mencegah kontaminasi silang halal/non-halal, dan regulasi pelabelan tidak mencakup ketentuan mengenai tanda halal yang diakui secara hukum. Kekurangan ini menciptakan ambiguitas bagi konsumen, tantangan bagi pelaku usaha, dan potensi konflik. Makalah ini mengusulkan perubahan legislatif pada Food Act dan regulasi terkait, beserta pembentukan kerangka kerja administratif yang kemungkinan besar berupa supervisi akreditasi nasional terhadap lembaga sertifikasi swasta, diatur oleh negara. Usulan-usulan tersebut bersumber dari yurisprudensi Islam (Maqasid al-Shari'ah dan prinsip Fikih) dan ditujukan untuk menjamin kepastian hukum, perlindungan konsumen yang lebih baik, fasilitasi perdagangan yang lebih baik, serta harmoni sosial dalam konteks multi-agama seperti di Sri Lanka.]